Bedside Teaching in Obstetrics and Gynecology - A. Clare, Camille; Yeh, John (Current Women's Health Reviews, 2013)
Bedside teaching is a commonly used educational tool in obstetrics and gynecology. In this clinical commentary, we analyzed and reviewed strategies for bedside teaching and guidelines for its use, and discussed its advantages and disadvantages. Electronic databases were searched for the period covering the years 2000 to 2012 for studies in the English language with the main outcome measure of the effectiveness of bedside teaching as an educational modality. There are no specific publications in the literature that address this issue in obstetrics and gynecology. Based on the literature in other settings, we infer that bedside teaching in obstetrics and gynecology is an effective teaching tool and should be studied further to determine its optimal usage as a teaching modality. The setting of labor and delivery is the most poignant example of bedside teaching in obstetrics and gynecology.
Keywords: labor and delivery